2017
DOI: 10.1504/wremsd.2017.080741
|View full text |Cite
|
Sign up to set email alerts
|

Co-production in business training in microfinance institutions: a conceptual approach

Abstract: Recent developments in service literature highlight the importance of co-production between the firm and the client in order to create value. This paper presents a model of co-production within the context of microfinance provision and investigates the dyadic relationship between Trainers from microfinance institutions (MFIs) and the Owner Managers of micro and small enterprises (MSEs). The paper develops a model that identifies the factors that facilitate co-production between Trainers and Owner Managers. It … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…The bulk of studies on education level and training show its positive influence, although there is some inconsistency in the results. Qualitative research conducted by Abeysekera et al (2017) found that the education of owner managers influenced their ability to follow the training. In Europe, the level of trainees' knowledge and skills was found to have a positive impact on entrepreneurship (Zamfir et al, 2018).…”
Section: Literature Review and Analytical Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…The bulk of studies on education level and training show its positive influence, although there is some inconsistency in the results. Qualitative research conducted by Abeysekera et al (2017) found that the education of owner managers influenced their ability to follow the training. In Europe, the level of trainees' knowledge and skills was found to have a positive impact on entrepreneurship (Zamfir et al, 2018).…”
Section: Literature Review and Analytical Frameworkmentioning
confidence: 99%
“…There is a growing consensus that entrepreneurship training offered to microentrepreneurs enables them to acquire knowledge, skills and attitudes (KSAs) that can be applied to improve clients' enterprise growth and sustainability (Gegenfurtner et al, 2020;Prediger & Gut, 2014). It is often argued that effective entrepreneurship training contributes considerably toward eliminating poverty by transforming the poor into successful microentrepreneurs (Abeysekera et al, 2017;Mihret Dessie & Shumetie Ademe, 2017). However, training initiatives face criticism of failure to enhance entrepreneurship in developing economies which exhibit enormous skill gaps (Awais Bhatti et al, 2013;Oware, 2020).…”
Section: Introductionmentioning
confidence: 99%